The Significance of the Contralateral Testis Size Measurement with Ultrasonography in Predicting Monorchism in Boys with Nonpalpable Testicles - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TARCAN, TUFAN; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2017)
Objective: The aim of this study was to determine the significance of contralateral testis size in predicting monorchism in pediatric patients with unilateral undescended testis. Materials and Methods: The data of patients who underwent surgical operation by a single pediatric urologist for undescended testis between 2013 and 2016 was evaluated retrospectively. The patients were grouped as having monorchism (M), nonpalpable intra-abdominal testis (NPIAT), and palpable undescended testis (PUDT). The dimensions of the testes were measured ultrasonographically and recorded before operation. Patients with nonpalpable testis underwent diagnostic laparoscopy and patients with PUDT underwent inguinal orchiopexy. Results: A total of 57 children with a mean age of 31 (11-60) months were evaluated. Of the children, 12 had M, 9 had NPIAT and 36 had PUDT with a similar mean age (p>0.05). The size of the descended testis was found to be significantly small in NPIAT* and PUDT** groups compared to the M group (*p<0.05, **p<0.001). However, the size of the undescended and descended testes was found to be similar between NPIAT and PUDT groups (p>0.05). Conclusion: The size of the testis in the scrotum might help to localize the position of the undescended testis.
Keywords: Monorchism; nonpalpable intra-abdominal testis; palpable undescended testis; testis; ultrasonography; UNDESCENDED TESTES; TESTICULAR VOLUME; IMPALPABLE TESTIS; CRYPTORCHIDISM; HYPERTROPHY; LAPAROSCOPY; ORCHIDOPEXY; MANAGEMENT; FERTILITY; CHILDREN